COMPREHENSIVE REVIEW ON EMPOWERING NURSING PRACTICE WITH INNOVATIONS, CHALLENGES, AND THE FUTURE OF PATIENT CARE - ‏Abdullah Mana Hutaylan Almahmde, ‏Shalwan Ali Zumaya Al Sharmah, ‏Ali Mana Hutailan Almuhmidhi, ‏Mana Rashed Mohammed Al Khamsan, ‏Mohammed Eidhah Bin Saeed Aldaghman, ‏Al Bahri, Dulaym Hadi (Chelonian Research Foundation, 2023)
This comprehensive review investigates how innovation s are making strides in patient care, tackling issues, and envisioning the end of nursing. Key themes explored include innovation, patient-centered care, and the effects of developing medicines. Comprehensive and precise written surveys give an understanding of the current circumstances. Proposals for a career in nursing are given. Fundamental discoveries highlight innovation in progressing execution, challenges in executing nursing mediations, and openings for future inquiry. Sessions centered on overcoming obstructions to unused practices, making steady administration, and planning caregivers for changing needs. Suggestions address speculations in instruction, collaborative associations, and arrangement promotion. In rundown, this review highlights the essential part of care innovation, advocates for collaborative innovation and patient-first care, and distinguishes modern conditions for making strides in understanding outcomes. Keywords: Nursing practice, innovations, challenges, patient care, technology, patient-centered care, healthcare trends